2013
DOI: 10.1186/1471-2350-14-92
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral muscular dystrophy and Charcot-Marie-Tooth neuropathy 1A - evidence for “double trouble” overlapping syndromes

Abstract: BackgroundWe report on a patient with genetically confirmed overlapping diagnoses of CMT1A and FSHD. This case adds to the increasing number of unique patients presenting with atypical phenotypes, particularly in FSHD. Even if a mutation in one disease gene has been found, further genetic testing might be warranted in cases with unusual clinical presentation.Case presentationThe reported 53 years old male patient suffered from walking difficulties and foot deformities first noticed at age 20. Later on, he deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Motor milestones delayed at 6 months with later manifestations of bilateral pes cavus, absent deep tendon reflexes, and sensory loss are indicative of CMT1A. Upon review of literature, Charcot-Marie-Tooth neuropathies in association with various forms of muscular dystrophy have been reported in four cases [10][11][12][13]. Butefisch et al first reported on a 22-year-old female who inherited both facioscapulohumeral muscular dystrophy (FSHD) and CMT1A from each of her parents leading to shortened life span and early death [11].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Motor milestones delayed at 6 months with later manifestations of bilateral pes cavus, absent deep tendon reflexes, and sensory loss are indicative of CMT1A. Upon review of literature, Charcot-Marie-Tooth neuropathies in association with various forms of muscular dystrophy have been reported in four cases [10][11][12][13]. Butefisch et al first reported on a 22-year-old female who inherited both facioscapulohumeral muscular dystrophy (FSHD) and CMT1A from each of her parents leading to shortened life span and early death [11].…”
Section: Discussionmentioning
confidence: 92%
“…Literature evidence shows alteration of disease course with worse prognosis in the presence of CharcotMarie-Tooth neuropathy and a muscular dystrophy [10,11,13]. Hence even if a mutation in a disease gene has been detected, further genetic testing may be warranted in unusual clinical presentations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…All had the core features of CMT4C, including demyelinating neuropathy with early‐onset scoliosis. There are reports of CMT4C patients presenting with side‐to‐side asymmetry, lack of scoliosis, and phenotypic variability despite identical genotypic mutations . Sleep apnea, respiratory failure, and cranial nerve involvement such as nystagmus and facial weakness have also been described in some patients …”
Section: Discussionmentioning
confidence: 99%
“…This is a further example of how a second mutation may modify the severity and presentation of genetic disorders within the same family and it stresses the importance to extend the genetic analysis on asymptomatic siblings. Other double-trouble phenotypes involving FSHD have been reported [4][5][6][7][8], but no one with motoneuron disease as second genetic disorder.…”
mentioning
confidence: 96%